Evangelism from the Margins: Experiences of the Ironic in Evangelism in Cardiff, UK. (July 2016) - Cruchley‐Jones, Peter
Abstract: This article arises from a presentation to the CWM/WCC Consultation, Explorations in Evangelism which took place in Sydney from 5 to 13 September 2015. There I shared the street art evangelism of my own congregation. However, in this article I want to explore how this street art evangelism is pointing us to the need for an appreciation of the ironic nature of evangelism, and consider evangelism from the margins. I explore this here as an aspect of the liberation missiology of the WCC's new ecumenical affirmation of mission: Together towards Life. But also show how it describes the historical roots of evangelism in the early church and captures the possibilities of evangelism now in a post‐Christian context like the UK. The article explores ideas and artwork as they invite an ironic appreciation of the countercultural nature of Christ's call to life, a call that questions the empires of Caesar and the church.